Peroxisome biogenesis, membrane contact sites, and quality control. (10th December 2018) - Farré, Jean‐Claude; Mahalingam, Shanmuga S; Proietto, Marco; Subramani, Suresh
Abstract: Peroxisomes are conserved organelles of eukaryotic cells with important roles in cellular metabolism, human health, redox homeostasis, as well as intracellular metabolite transfer and signaling. We review here the current status of the different co‐existing modes of biogenesis of peroxisomal membrane proteins demonstrating the fascinating adaptability in their targeting and sorting pathways. While earlier studies focused on peroxisomes as autonomous organelles, the necessity of the ER and potentially even mitochondria as sources of peroxisomal membrane proteins and lipids has come to light in recent years. Additionally, the intimate physical juxtaposition of peroxisomes with other organelles has transitioned from being viewed as random encounters to a growing appreciation of the expanding roles of such inter‐organellar membrane contact sites in metabolic and regulatory functions. Peroxisomal quality control mechanisms have also come of age with a variety of mechanisms operating both during biogenesis and in the cellular response to environmental cues. Abstract : Peroxisomes have important roles in cellular metabolism, human health, redox homeostasis, intracellular metabolite transfer and signalling. This comprehensive review discusses how peroxisomes are generated, how they communicate with other organelles and how quality control mechanisms operate to maintain their homeostasis.